Is experience on a farm an effective approach to understanding animal products and the management of dairy farming?. (25th August 2013) - Mochizuki, Mariko; Osada, Masahiro; Ishioka, Katsumi; Matsubara, Takako; Momota, Yutaka; Yumoto, Norio; Sako, Toshinori; Kamiya, Shinji; Yoshimura, Itaru
Abstract The understanding of animal products and dairy farming is important for the promotion of dairy farming. Thus, to examine the effects of farm experience on the understanding of animal products and the management of dairy farming, the interaction between students and dairy cows was investigated in groups of first‐year veterinary nursing students in 2011 and 2012 (n = 201). These students included 181 women and 20 men. Nine items about dairy cows were presented in a questionnaire. The survey was performed before and after praxis on the educational farm attached to the authors' university. After praxis on the farm, increases occurred in the number of positive responses to the items involving the price of milk, dairy farming and the taste of milk. For these items, a significant difference (P < 0.05) was found between the scores obtained before and after training. The results of the study suggested that farm experience is useful for improving the understanding of animal products and dairy farming.